The effects of state ownership in the internationalization of emerging multinationals - Arreola, Maria Fernanda (2014)
This thesis is a collection of three different research projects analyzing the effect of state ownership in the internationalization of Emerging Multinationals (EMNEs). The participation of the state as shareholder is a phenomenon that can bring new light into the governance, management and strategic impact of having states participate as owners in different levels. These studies will allow us to explore, from different perspectives, the extent to which states, while owners, can impact the EMNE. The studies thee contained go from exploring the selection mechanisms for a firm to become the target of state ownership to its effect on the internationalization pace, passing through the revision of the mechanisms available for the state to gain control and access to a firm’s decision making, through changes to its corporate governance.